2007
DOI: 10.1007/s00419-007-0119-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of leakage flow through labyrinth seals on rotordynamics: numerical calculations and experimental measurements

Abstract: An extensive investigation of the influence of the leakage flow through a labyrinth seal at supply pressure of 12 bar on the rotordynamics was performed by using numerical calculations and experimental measurements. Toward this end, an experimental rotor setup was established in Shanghai Jiao Tong University. Two labyrinth seals were chosen for comparison, e.g., an interlocking seal and a stepped one. The numerical calculations based on the bulk-flow theory and the perturbation analysis were accomplished. Simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The unsteady static pressure in cavities of the interlock seal, which was numerically calculated by employing perturbation analysis, was demonstrated to be in favorable agreement with experimental measurements by Liu et al [10]. The above-mentioned linear model was reduced from a preconditioned track of the whirling rotor, which slightly deviates from the statically balanced position; otherwise, the nonlinear behaviors of the whirling rotor, e.g., lock-on frequency and kick amplitude, could not be accurately captured by the linearized force-displacement model [2][3][4][9][10][11]. Hua et al [12] and Cheng et al [13] carried out nonlinear analysis of the rotordynamics associated with leakage air flow through a simple annular seal by using the Muzynska model [14].…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…The unsteady static pressure in cavities of the interlock seal, which was numerically calculated by employing perturbation analysis, was demonstrated to be in favorable agreement with experimental measurements by Liu et al [10]. The above-mentioned linear model was reduced from a preconditioned track of the whirling rotor, which slightly deviates from the statically balanced position; otherwise, the nonlinear behaviors of the whirling rotor, e.g., lock-on frequency and kick amplitude, could not be accurately captured by the linearized force-displacement model [2][3][4][9][10][11]. Hua et al [12] and Cheng et al [13] carried out nonlinear analysis of the rotordynamics associated with leakage air flow through a simple annular seal by using the Muzynska model [14].…”
Section: Introductionsupporting
confidence: 63%
“…Subsequently, the rotordynamics coefficients associated with the leakage air flow through various labyrinth seals were numerically determined, e.g., the straight-through seal [1, 2, 7 and 8], the stepped seal [3,4] and the honeycomb seal [9]. The unsteady static pressure in cavities of the interlock seal, which was numerically calculated by employing perturbation analysis, was demonstrated to be in favorable agreement with experimental measurements by Liu et al [10]. The above-mentioned linear model was reduced from a preconditioned track of the whirling rotor, which slightly deviates from the statically balanced position; otherwise, the nonlinear behaviors of the whirling rotor, e.g., lock-on frequency and kick amplitude, could not be accurately captured by the linearized force-displacement model [2][3][4][9][10][11].…”
Section: Introductionmentioning
confidence: 83%
“…The in-depth evaluation of the rotordynamics of the high-pressure rotor of a 1,000 MW ultra-supercritical steam turbine associated with steam leakage through labyrinth seals was made according to the first critical speed, ω cr , and the logarithmic decrement of the rotor vibration, δ, which was determined from Eq. (11). The destabilization of the rotor system associated with steam flow through the labyrinth seals is fundamentally analyzed in terms of the radial force and the frictional force, which are the major components of the aerodynamic forcing on the rotor.…”
Section: Resultsmentioning
confidence: 99%
“…The destabilization of the rotor system associated with steam flow through the labyrinth seals is fundamentally analyzed in terms of the radial force and the frictional force, which are the major components of the aerodynamic forcing on the rotor. The radial force entails deformation of the rotor and is equalized by the elastic force of the rotor, while the frictional force accelerates the whirling motion of the rotor [11]. When the positive work exerted on the rotor by frictional force is larger than the dissipation energy consumed by the external damping force, destabilization of the rotor is triggered [12].…”
Section: Resultsmentioning
confidence: 99%
“…Further more, a set of differential equations were employed to allow the clear flow structure of the leakage air flow through a straight-labyrinth seal [13,14]. Recently, Liu et al [15] convincingly demonstrated deterioration of the rotor stability due to aerodynamic forcing of the leakage air flow through an interlocking labyrinth seal. Recall that the major concern of most previous experimental and numerical endeavors was related to leakage air flow through labyrinth seal.…”
Section: Introductionmentioning
confidence: 98%